Discovery of prolyl hydroxylase 2 inhibitors with new chemical scaffolds as in vivo active erythropoietin inducers through a combined virtual screening strategy. (7th November 2019) - Yu, Zhan; Li, Zhihong; Yu, Quanwei; Wang, Zhi; Song, Huilin; Sun, Hanyu; Fan, Rufeng; Bi, Angzhi; Zhang, Jun; Zhang, Xiaojin
Abstract: Hypoxia‐inducible factor (HIF) is identified to be a promising target to mediate the response to hypoxia. Its stability and activation are negatively controlled by prolyl hydroxylase 2 (PHD2). Thus, PHD2 inhibition has been perceived as a promising anti‐anemia therapy. In this study, we carried out a structure‐based virtual screening followed by in vitro and in vivo biological validation, with the goal to identify novel PHD2 inhibitors. As a result, a set of hits with new chemical scaffolds were revealed to be active in vitro for PHD2 inhibition. Compounds 2 and 3 were revealed to be capable of stabilizing HIF‐α and stimulating erythropoietin (EPO) expression in cell‐based assays. Notably, further in vivo assays revealed that 2 was capable of elevating the EPO plasma levels in C57BL/6 mice model. These findings provide new chemical scaffolds for further development of PHD2 inhibitors. Abstract : Application of 2 to C57BL/6 mice enabled increases the level of EPO. Taken together, compound 2 is sufficiently potent to constitute new potential scaffold for PHD2 inhibition and it would be possible to provide useful information for the development of new chemical entities targeting PHD2.